Peran PAI Dalam Pembentukan Karakter Siswa: Analisis Di SMA Swasta Istiqlal Delitua - Zuhri, Mutiara; Mavianti, Mavianti (EL-EMIR Institute, 2025)
Islamic Religious Education (PAI) is a foundational subject in Indonesia, essential for molding students' character and moral compass. This research focuses on its role in character development at SMAS Istiqlal Deli Tua. Using a qualitative descriptive method, data were gathered through observation, interviews, and documentation. The results show that PAI teachers serve multiple functions: they are educators, role models, motivators, and mentors who help students internalize Islamic values. The study highlights several key strategies, such as integrating religious habits into daily life, reinforcing the teacher's role as an example, incorporating Islamic values into lessons and extracurriculars, and collaborating with parents. These methods are crucial for fostering students' religious awareness, discipline, social responsibility, and empathy. Despite modern challenges like the influence of social media, PAI remains a vital force in shaping student character in today's digital age.